Test-retest reliability of the 30-15 Intermittent Fitness Test: A systematic review - Grgic, J.; Lazinica, B.; Pedisic, Z. (Journal of Sport and Health Science, 2021)
Purpose: This review aimed to synthesize previous findings on the test retest reliability of the 30 15 Intermittent Fitness Test (IFT).Methods: The literature searches were performed in 8 databases. Studies that examined the test retest reliability of the 30 15 IFT and presentedthe intraclass correlation coefficient (ICC) and/or the coefficient of variation (CV) for maximal velocity and/or peak heart rate were included.The consensus-based standards for the selection of health measurement instruments (COSMIN) checklist was used for the assessment of the methodological quality of the included studies.Results: Seven studies, with a total of 10 study groups, explored reliability of maximal velocity assessed by the 30 15 IFT. ICCs ranged from0.80 to 0.99, where 70% of ICCs were§0.90. CVs for maximal velocity ranged from 1.5% to 6.0%. Six studies, with a total of 7 study groups,explored reliability of peak heart rate as assessed by the 30 15 IFT. ICCs ranged from 0.90 to 0.97 (i.e., all ICCs were >=0.90). CVs rangedfrom 0.6% to 4.8%. All included studies were of excellent methodological quality.Conclusion: From the results of this systematic review, it can be concluded that the 30 15 IFT has excellent test retest reliability for both max-imal velocity and peak heart rate. The test may, therefore, be used as a reliable measure of fitness in research and sports practice.